Identification of phlebotomine sand flies using one MALDI-TOF MS reference database and two mass spectrometer systems - Mathis, Alexander; Depaquit, Jérôme; Dvořák, Vit; Tuten, Holly; Bañuls, Anne-Laure; Halada, Petr; Zapata, Sonia; Lehrter, Véronique; Hlavačková, Kristýna; Prudhomme, Jorian; Volf, Petr; Sereno, Denis; et al. (Parasites & vectors, 2015)
BACKGROUND: Rapid, accurate and high-throughput identification of vector arthropods is of paramount importance in surveillance programmes that are becoming more common due to the changing geographic occurrence and extent of many arthropod-borne diseases. Protein profiling by MALDI-TOF mass spectrometry fulfils these requirements for identification, and reference databases have recently been established for several vector taxa, mostly with specimens from laboratory colonies. METHODS: We established and validated a reference database containing 20 phlebotomine sand fly (Diptera: Psychodidae, Phlebotominae) species by using specimens from colonies or field-collections that had been stored for various periods of time. RESULTS: Identical biomarker mass patterns ('superspectra') were obtained with colony- or field-derived specimens of the same species. In the validation study, high quality spectra (i.e. more than 30 evaluable masses) were obtained with all fresh insects from colonies, and with 55/59 insects deep-frozen (liquid nitrogen/-80 °C) for up to 25 years. In contrast, only 36/52 specimens stored in ethanol could be identified. This resulted in an overall sensitivity of 87 % (140/161); specificity was 100 %. Duration of storage impaired data counts in the high mass range, and thus cluster analyses of closely related specimens might reflect their storage conditions rather than phenotypic distinctness. A major drawback of MALDI-TOF MS is the restricted availability of in-house databases and the fact that mass spectrometers from 2 companies (Bruker, Shimadzu) are widely being used. We have analysed fingerprints of phlebotomine sand flies obtained by automatic routine procedure on a Bruker instrument by using our database and the software established on a Shimadzu system. The sensitivity with 312 specimens from 8 sand fly species from laboratory colonies when evaluating only high quality spectra was 98.3 %; the specificity was 100 %. The corresponding diagnostic values with 55 field-collected specimens from 4 species were 94.7 % and 97.4 %, respectively. CONCLUSIONS: A centralized high-quality database (created by expert taxonomists and experienced users of mass spectrometers) that is easily amenable to customer-oriented identification services is a highly desirable resource. As shown in the present work, spectra obtained from different specimens with different instruments can be analysed using a centralized database, which should be available in the near future via an online platform in a cost-efficient manner.
Keywords: Animals; Electron Transport Complex IV; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; teplota; Molecular Sequence Data; respirační komplex IV; Sensitivity and Specificity; entomologie; hmyzí proteiny; senzitivita a specificita; Psychodidae; Temperature; molekulární sekvence - údaje; Entomology; Sequence Analysis, DNA; Insect Proteins; spektrometrie hmotnostní - ionizace laserem za účasti matrice; zvířata; sekvenční analýza DNA